P204 Reducing antigen exposure in pigeon breeders. Wearing a mask is a sign of disease. (14th November 2013) - McHugh, K; Fraser, I; Bourke, S; McSharry, C; Lynch, P; Anderson, K
Abstract : Advice to pigeon breeders from the British Pigeon Fanciers Medical Research website includes methods to reduce dust exposure: as well as increasing loft ventilation, it recommends that a respirator is worn while in the loft. A field survey of the use of masks for this purpose found up to 40% usage amongst breeders (n = 258). Studies in small numbers of HP patients demonstrated reducing symptom response following inhalation provocation tests as well as reducing serum antibody levels (1). Despite the potential benefit of wearing masks, and the apparent willingness of pigeon fanciers to do this, little is known about their protective value in HP. The aim of this study is to compare survey results since 1991, and to examine the relationship between diagnosis of pigeon breeder's disease (PBD), serology, spirometry and mask wearing. Our 1997 survey (n = 252) showed that 51% would use a mask. In our 2013 survey (n = 188), we had a response of 54%. Those wearing a mask have higher IgG (mcg/ml) antibody levels (interquartile range 0.92–16.33 median 4.96 –v- 3.02–17.04 median 8.55, p = 0.047). Questionnaire symptom responses, spirometry, as well as useful radiology (CT scanning) or biopsy were used to grade the likelihood of PBD as unlikely (n = 99), maybe (57) or likely (32). Mask wearing was associated with likelihood of PBD (p = 0.068). Those with symptoms (n = 46) or minimal symptoms (n = 38) performed spirometry. Analysis showed an apparent trend amongst subjects with a restrictive defect to be more marked amongst mask wearers–70% (n = 16) being moderate/severely restricted–compared to 43% non mask wearers (Chi-sq = 2.62, p = 0.105). We interpret these findings as evidence that mask wearing is much more likely after symptoms have appeared in pigeon breeders: not the pattern we expected of mask wearing (or dust avoidance) to prevent the development of the disease. Paradoxically, mask wearing in pigeon breeders may also be an unreported sign of PBD. References: Hendrick, D J (1981) Protective value of dust respirator in extrinsic alveolitis: clinical assessment using inhaltion provocation tests. Thorax. 36: 917–921